Emotion Exploration of Students at State University of Malang in Sprachkompetenz Deutsch II Course - Aisyah Intan Laksono; Iwa Sobara (Nexus Publishing, 2025)
This research aims to find out the various positive and negative emotions experienced by students, and the factors that cause these emotions to appear in the context of learning. The method used in this research is descriptive qualitative, with data collection techniques using a questionnaire adapted from the Achievement Emotions Questionnaire (AEQ) and interviews. The results of this study show that most students tend to feel positive emotions when learning in class and receiving grades/results. Meanwhile, they dominantly feel negative emotions when facing exams. The focus of this study is on students taking Sprachkompetenz Deutsch II, which has not received much attention in previous studies. However, this study has not explored academic experiences in other courses, which may give rise to different emotional dynamics. The findings of this study contribute to understanding the role of students' emotions in Sprachkompetenz Deutsch II and can serve as a reference for teachers to design teaching methods that are more sensitive to students' emotions.